Cannabiorcol as a novel inhibitor of the p38/MSK-1/NF-κB signaling pathway, reducing matrix metalloproteinases in osteoarthritis - Jeon, Youngsic; Kim, Jiyool; Kwon, Hyukjoon; Yeon, Young Joo; Kim, Taejung; Ham, Jungyeob; Kim, Young-Joo (Elsevier BV, 2024)
Background The bioactivity and potential medicinal applications of cannabiorcol, a lesser-known derivative of Cannabis sativa, require further investigation. Osteoarthritis (OA) is a chronic joint condition marked by gradual degradation of the cartilage and commonly associated with elevated levels of matrix metalloproteinases (MMPs). However, the influence of cannabiorcol on OA and its underlying mechanisms remains unclear. Methods In silico analysis investigated the key transcription factors that regulate MMP expression. A chondrocyte cell model [interleukin (IL)-1β and IL-1？-treated C20A4 cell line] was established and treated with cannabiorcol. Associated cytotoxicity was assessed using a WST-8 assay. A monoiodoacetate-induced OA rat model was established and treated with cannabiorcol. Protein translocation and transactivation analyses were conducted using immunofluorescence and dual-luciferase reporter assays, respectively. Western blotting and real-time PCR analyzed relevant markers to examine cannabiorcol's effects on OA and its fundamental mechanisms. Results Cannabiorcol inhibits the expression of IL-1β-induced MMPs compared to other cannabis-related compounds. In silico analysis revealed that the nuclear factor-kappa β (NF-κβ) and mitogen-activated protein kinase (MAPK) pathways are associated with MMP expression as key regulators. In vitro, cannabiorcol inhibits the NF-κB and p38 MAPK pathways independently cannabinoid receptors and transient receptor potential vanilloids. In vivo, cannabiorcol reduces MMP expression and ameliorates monoiodoacetate-induced OA traits in rats. Conclusion Cannabiorcol inhibits IL-1β-induced MMP expression in vitro and alleviates OA in an MIA-induced OA rat model by reducing MMP expression and inhibiting the p65/p38 axis.